Eribulin in heavily pretreated metastatic breast cancer patients and clinical/biological feature correlations: impact on the practice. (February 2015) - Fabi, Alessandra; Moscetti, Luca; Ciccarese, Mariangela; Caramanti, Miriam; Salesi, Nello; Verde, Nicla La; Russillo, Michelangelo; Generali, Daniele; Scandurra, Giuseppina; Vari, Sabrina; Pacetti, Umberto; Cognetti, Francesco; et al.
ABSTRACT : Aim: This multicenter study describes the effectiveness of eribulin in current practice.Patients & methods: In total, 78 patients with advanced metastatic breast cancer, previously treated with two or more chemotherapy lines were enrolled.Results: The median duration of response and disease stability were 7.5 (5.4–9.5) and 8.9 (6.2–11.6) months, respectively, with a clinical benefit (CB) at 6 months in 41% of patients. CB in visceral and nonvisceral metastases were 72.7 and 88.9%, respectively. Eribulin was active also in brain metastases, with 47% CB. The activity was shown in all biological subtypes. Toxicities were manageable.Conclusion: Our study confirms the effectiveness of eribulin mesylate in the treatment of patients with metastatic breast cancer and two or more lines of chemotherapy, in particular in the good disease control at the different metastatic sites.